Prototype Robot Pemadam Api Beroda Menggunakan Teknik Navigasi Wall Follower - Ery Safrianti; Rahyul Amri; Septian Budiman (Universitas Syiah Kuala, 2012)
Fire Robot serves to detect and extinguish the fire. The robot is controlled by the microcontroller ATMEGA8535 automatically. This robot contains of several sensors, such as 5 sets of ping parallax as a robot navigator, a set UVTron equipped with fire-detecting driver, DC motor driver L298 with two DC servo motors. The robot was developed from a prototype that has been studied previously with the addition on the hardware side of the sound activation and two sets of line detector. The robot will active if it receives input from the sound activation unit and will start to find the fire with “search the wall” navigation techniques. The line sensor was used as a door and home detector and circle the fire area.To extinguish the fire, this robot uses a fan driven by a BD139 transistor circuit. The overall test results show that the robot can detect the presence of the fire in each room. The robot also can find the fire and extinguish it within 1 minute.